Synopsis of the carpenter bee subgenus Xylocopa (Schonnherria) Lepeletier, 1841 (Hymenoptera: Apidae) in Colombia, with designation of lectotypes and the description of two new species - Villamizar, Germán; Fernández, Fernando; Vivallo, Felipe (Zootaxa, 2020)
A synopsis of the metallic carpenter bees Xylocopa subgenus Schonnherria Lepeletier in Colombia is presented. Eleven species were recognized: X. dimidiata Latreille, X. ecuadorica Cockerell, X. lateralis Say, X. lucida Smith, X. metallica Smith, X. muscaria (Fabricius), X. ornata Smith, X. viridis Smith, and X. simillima Smith, being this latter a new record for the country. In addition, two new species are described: X. auriventris n. sp. and X. romeroi n. sp. from the Colombian Andean and Pacific region, respectively. To stabilize the application of some names, lectotypes were designated for X. binotata Pérez (=X. lateralis), X. muscaria, X. ornata, X. simillima and X. viridis. Diagnoses, descriptions, comments, floral records, distribution maps, figures and an identification key are also provided.